2019
DOI: 10.1063/1.5086045
|View full text |Cite
|
Sign up to set email alerts
|

Thermal fluctuation noise in Mo/Au superconducting transition-edge sensor microcalorimeters

Abstract: In many superconducting transition-edge sensor (TES) microcalorimeters, the measured electrical noise exceeds theoretical estimates based on a thermal model of a single body thermally connected to a heat bath. Here, we report on noise and complex impedance measurements of a range of designs of TESs made with a Mo/Au bilayer. We have fitted the measured data using a two-body model, where the x-ray absorber and the TES are connected by an internal thermal conductance G ae . We find that the so-called excess nois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 36 publications
5
32
0
Order By: Relevance
“…As suggested and observed in many experiments [50][51][52][53][54], a single-body thermal model for a TES calorimeter is rarely sufficient to explain the detector response. This is due to the presence of dangling heat capacitance and parasitic thermal conductance in the TES-absorber structures or to a not sufficiently high thermal conductance between TES and absorber.…”
Section: Tes Electro-thermal Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested and observed in many experiments [50][51][52][53][54], a single-body thermal model for a TES calorimeter is rarely sufficient to explain the detector response. This is due to the presence of dangling heat capacitance and parasitic thermal conductance in the TES-absorber structures or to a not sufficiently high thermal conductance between TES and absorber.…”
Section: Tes Electro-thermal Equationsmentioning
confidence: 99%
“…It can be shown that a two-body model [49,50,53], as drawn in Figure 1b, is sufficiently general to account for parasitic thermal effects in TES-based detectors. A more detailed analysis for even more complex thermal structures can be found in [51][52][53][54]. However, one has to keep in mind that the model is unconstrained when too many thermal bodies are added into the system of equations.…”
Section: Tes Electro-thermal Equationsmentioning
confidence: 99%
“…Here k B is Boltzmann's constant and M 2 is the excess noise, given by the difference between the measured and predicted noise. This excess noise is typically explained by other noise sources, such as the weak-link effect described by the resistively shunted junction (RSJ) model 20,45 , the presence of phase-slip lines 46 , or ITFN 11,15,[47][48][49] . In this paper, we will not go into a detailed analysis of the origin of the excess noise, but instead use it as a guideline to find the optimal TES design.…”
Section: Excess Noisementioning
confidence: 99%
“…Traditionally, TESs used for X-ray calorimetry have been pushed to low resistance values (R n 10 mΩ). This type of device is very suitable for the DC-biased TDM readout since they typically have very sharp superconducting transitions and low internal thermal fluctuation noise between different parts of the calorimeter 15 , leading to very good energy resolution 8 . However, these low-Ohmic devices are generally unsuited for AC-biased readout.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation